A tale of agriculturalists and hunter‐gatherers: Exploring the thrifty genotype hypothesis in native South Americans. Issue 3 (2nd May 2017) - Reales, Guillermo; Rovaris, Diego L.; Jacovas, Vanessa C.; Hünemeier, Tábita; Sandoval, José R.; Salazar‐Granara, Alcibiades; Demarchi, Darío A.; Tarazona‐Santos, Eduardo; Felkl, Aline B.; Serafini, Michele A.; Salzano, Francisco M.; Bisso‐Machado, Rafael; et al.
Abstract: Objectives: To determine genetic differences between agriculturalist and hunter‐gatherer southern Native American populations for selected metabolism‐related markers and to test whether Neel's thrifty genotype hypothesis (TGH) could explain the genetic patterns observed in these populations. Materials and Methods: 375 Native South American individuals from 17 populations were genotyped using six markers ( APOE rs429358 and rs7412; APOA2 rs5082; CD36 rs3211883; TCF7L2 rs11196205; and IGF2BP2 rs11705701). Additionally, APOE genotypes from 39 individuals were obtained from the literature. AMOVA, main effects, and gene‐gene interaction tests were performed. Results: We observed differences in allele distribution patterns between agriculturalists and hunter‐gatherers for some markers. For instance, between‐groups component of genetic variance ( F CT ) for APOE rs429358 showed strong differences in allelic distributions between hunter‐gatherers and agriculturalists ( p  = 0.00196). Gene‐gene interaction analysis indicated that the APOE E4/ CD36 TT and APOE E4/ IGF2BP2 A carrier combinations occur at a higher frequency in hunter‐gatherers, but this combination is not replicated in archaic (Neanderthal and Denisovan) and ancient (Anzick, Saqqaq, Ust‐Ishim, Mal'ta) hunter‐gatherer individuals. Discussion: A complex scenario explains the observed frequencies of the tested markers in hunter‐gatherers. Different factors, such as pleotropic alleles, rainforest selective pressures, and population dynamics, may be collectively shaping the observed genetic patterns. We conclude that although TGH seems a plausible hypothesis to explain part of the data, other factors may be important in our tested populations.